Influence of Re on the Properties of a NiCoCrA1Y Coating Alloy - J.J. Liang H. We Y.L. Zhu X.F. Sun Z.Q. Hu M.S. Dargusch X.D. Yao (材料科学技术学报：英文版, 2011)
MCrAIY can serve as stand-alone overlay coatings or bond coats in thermal barrier coating systems, and its properties play a vital role in determining the performance of these coating systems. In order to further understand the behavior of MCrAIY coatings, several NiCoCrAIY model alloys with different levels of Re （0.3 wt%, O wt%, and 9 wt%） were investigated. Microstructural observation showed the addition of Re promoted the precipitation of Cr-rich phases, such as α-Cr and σ. The presence of α-Cr lowered the coefficient of thermal expansion （CTE） of the coating alloys, which could reduce the CTE mismatch at the scale-metal interface. The solid solution strengthening effect of Re is responsible for an increase in Rockwell hardness of the coating alloys. But the isothermal oxidation resistance at 1100℃ was deteriorated due to the precipitation of brittle α-Cr phase, a phase of inferior oxidation resistance compared with β-NiAI and γ-Ni.